Changes in anthropometrics and biochemical parameters in bariatric surgery patients post both subject to diet therapy - Lima, Alysson Diego Pereira de (2012)
Actually the bariatric surgery is considered the most efficient weight reduction treatment and maintenance of the weight loss in patients with morbid obesity. The aim of this work is to verify the anthropometric alteration and biochemistries in two individuals submitted to the bariatric surgery. There is a consensus in the literature that the bariatric surgery is considered the most efficient weight reduction and maintenance treatment of weight loss in serious patients. The sample is composed by two patients of both sexes. A data collection was accomplished in the pre and postoperative, in that were verified: anthropometric data, waist and hip circumference, complete blood count tests, glicemyc, total cholesterol, HDL, LDL, triglyceride) type and frequency of physical activity. With that post-chirurgic food must contain a re-education and constant physical exercises to ensure that the patient can maintain a healthy weight. In spite of interesting results found in the present investigation after Bariatric, studies indicate that constant physical exercises for individuals post-chirurgic provides an improvement in biochemical and anthropometrics.